THE SPECIFICITY AND COMPLEXITY OF THE PROCESS OF LEARNING ENGLISH - Khodjayev K. K. (International Journal on Orange Technologies, 2021)
This article discusses the specificity and complexity of the process of learning English. Methodological assistance and recommendations were provided to English language learners.